2015
DOI: 10.1007/s00213-015-4057-0
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing and neurochemical effects of the “bath salts” constituents 3,4-methylenedioxypyrovalerone (MDPV) and 3,4-methylenedioxy-N-methylcathinone (methylone) in male rats

Abstract: Rationale 3,4-Methylenedioxypyrovalerone (MDPV) and 3,4-methylenedioxy-N-methylcathinone (methylone) are synthetic drugs found in so-called “bath salts” products. Both drugs exert their effects by interacting with monoamine transporter proteins. MDPV is a potent uptake blocker at transporters for dopamine and norepinephrine while methylone is a non-selective releaser at transporters for dopamine, norepinephrine and serotonin (5-HT). Objectives We hypothesized that prominent 5-HT-releasing actions of methylon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(111 citation statements)
references
References 37 publications
10
98
1
Order By: Relevance
“…Consistent with previous work (Baumann et al, 2012;Schindler et al, 2016), we found that methylone produced dose-related elevations in extracellular dopamine and 5-HT in rat nucleus accumbens, with larger effects on extracellular 5-HT. Importantly, the iv doses of methylone tested here in microdialysis experiments are in the range of those self-administered by rats (Schindler et al, 2016;Vandewater et al, 2015;Watterson et al, 2012). Administration of MDC increased dopamine and 5-HT as well, but weakly compared with methylone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous work (Baumann et al, 2012;Schindler et al, 2016), we found that methylone produced dose-related elevations in extracellular dopamine and 5-HT in rat nucleus accumbens, with larger effects on extracellular 5-HT. Importantly, the iv doses of methylone tested here in microdialysis experiments are in the range of those self-administered by rats (Schindler et al, 2016;Vandewater et al, 2015;Watterson et al, 2012). Administration of MDC increased dopamine and 5-HT as well, but weakly compared with methylone.…”
Section: Discussionsupporting
confidence: 92%
“…In vivo studies in rats demonstrate that methylone increases extracellular concentrations of dopamine and 5-HT in the brain, with greater effects on 5-HT (Baumann et al, 2012;Schindler et al, 2016). The mechanism of action for methylone resembles that of MDMA, which is not surprising considering methylone is the β-keto analog of MDMA.…”
Section: Introductionmentioning
confidence: 86%
“…Specifically, MDPV blocks cellular uptake of dopamine (DA) and norepinephrine (NE) by binding to presynaptic transporters (Baumann et al 2013). Preclinical studies find that MDPV elevates locomotor activity, primes reward threshold during intracranial self-stimulation, induces place preference, and is readily self-administered intravenously (Bonano et al 2014; Nguyen et al 2016; Schindler et al 2016; Simmons et al 2016; Watterson et al 2014). At high doses, “bizarre behaviors” can be observed in rats following acute injection of synthetic cathinone drugs including sporadic jumping while facing away from chamber wall, retropulsion and flattened body posture (Marusich et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it seems plausible that formation of these same phase I metabolites could also impact the reinforcing effects of MDPV, suggesting that route of administration may be an important factor to consider when evaluating the abuse liability of this compound. Intravenous self-administration of MDPV has been described in rats (e.g., Watterson et al, 2012; Aarde et al, 2013, 2015a, 2015b; Schindler et al, 2016; Gannon et al, 2017), however there is a paucity of information related to the abuse-related effects of orally administered MDPV. The aims of the current study were therefore (1) to determine whether concentrations of MDPV would elicit locomotor stimulant effects, (2) to determine whether MDPV is preferentially chosen over alternative fluids in a 2-bottle choice paradigm, (3) to use conditioned place preference (CPP) to determine whether voluntary consumption of a preferred MDPV concentration with locomotor stimulant effects would also induce appetitive stimulus effects, and (4) to determine whether any observed appetitive stimulus effects are similar to those observed following IP administration of MDPV.…”
Section: 0 Introductionmentioning
confidence: 99%